Bioactivity-Guided Isolation of Antiproliferative Sesquiterpene Lactones from Centaurea solstitialis L. ssp. solstitialis - Erenler, Ramazan; Sen, Ozkan; Sahin Yaglioglu, Ayse; Demirtas, Ibrahim (Combinatorial Chemistry & High Throughput Screening, 2016)
Centaurea solstitialis L. ssp. solstitialis (CSS) has been used as medicine for various diseases. In this work, root, stem and flower parts of the plant were separately extracted with methanol to execute bioassay-guided isolation. Antiproliferative activities of each extracts on C6 cells (Rat Brain tumor cells) and HeLa cells (human uterus carcinoma) were investigated in vitro. The methanol extract of stem exhibited the most antiproliferative activity therefore isolation of active compounds was carried out for stem of the plant. Methanol extract of stem was boiled at 97 °C for 2 hours in water and then hexane and ethyl acetate were extracted sequentially. Solstitialin A 1 and 15-dechloro-15-hydroxychlorojanerin 2 were isolated from ethyl acetate extract by column chromatography and identified by spectroscopic techniques. Solstitialin A 1 was isolated from CSS and 15-dechloro-15-hydroxychlorojanerin 2 was isolated from Saussurea lipschitz and Rhaponticum pulchrum previously. These two compounds exhibited very high antiproliferative activity on C6 and HeLa cells. IC50 and IC75 values of compound 1 were obtained as 10.78 and 53.65 against C6 cell and as 48.78 and 68.52 against HeLa, respectively. IC50 and IC75 values of compound 2 were determined as 432.43 and 109.79 against C6 cell.
Keywords: 15-dechloro-15-hydroxychlorojanerin